Pengobatan transfer energi sebagai salah satu metode pengobatan tradisional dalam penyembuhan penyakit - Annisa Novitasari; Myrtati D Artaria (Masyarakat, Kebudayaan dan Politik, 2015)
Nowadays, traditional medicine has been a widely spreaded phenomena in society as alternative or supplement aside of modern medication. Energy-transfer medication is one kind of traditional medication which become popular in the society, even no specific medicine or medical devices used in this treatment. The research method used were observation and interview. Interview was conducted to two informant as energy-transfer performer and six patients of this medication. The research shows that the use of energy-transfer medication was influenced by disease severity level, knowledge and experience, faith, social, and distance.